Information Policy in Tournaments with Sabotage1. (19th June 2013) - Gürtler, Oliver; Münster, Johannes; Nieken, Petra
Abstract Sabotage is one of the main problems of tournament‐like reward schemes. Workers who are leading in a tournament are more dangerous rivals, and are therefore sabotaged more heavily. This implies that there is an extra cost to becoming a leader and, hence, to choosing high productive effort in the early stages of a tournament. The incentives to exert productive effort are thereby reduced. We show that this problem can be solved by concealing intermediate information on the performances of workers (i.e., by clever information management). Moreover, we offer experimental evidence indicating that such information management does increase productive efforts.